Scaffolding Learning Strategy on Students' Problem Solving Abilities Material on Lines and Series - Rif'ah, Hafidlotul; Suprihatin, Suprihatin; Purwati, Heni; Muhtarom, Muhtarom (Lembaga Pendidikan Hikmatun Najah Blora, 2024)
Problem solving is an ability that students need to master in learning mathematics. Each student has different problem solving abilities. Student errors in problem solving mean that students do not understand the material well. One of the supports that teachers can provide is through scaffolding (assistance). Scaffolding is provided according to student needs related to students' problem solving abilities. The purpose of this article is to describe scaffolding as an effort to help students in solving mathematical problems regarding sequences and series. This research is a qualitative descriptive study which aims to describe scaffolding as an effort to help students in solving mathematical problems regarding sequences and series. The students involved in this research were class Meanwhile, the research subjects were 2 students taken from the understanding mapping group who needed assistance, namely AD and ZA. Data collection techniques through tests and interviews. The data analysis technique follows the Miles and Huberman model by testing the validity of the triangulation data technique. The research results show that there are errors in the problem solving process. Therefore, the scaffolding provided with the explaining, reviewing, and restructuring stages can help students in solving mathematical problems. Based on research, providing scaffolding can be used as a solution for students to overcome errors in solving problems